Comparison of impact performance between youth and varsity football helmets. (December 2017) - Sproule, David W; Rowson, Steven
Current youth football helmets, intended for players under the age of 14 years, are similar in design and are tested according to the same standards as varsity football helmets. This study evaluated the impact performance of comparable youth and adult varsity football helmets. Eight youth and eight varsity helmet models were evaluated using an impact pendulum with a modified National Operating Committee on Standards for Athletic Equipment medium-sized headform mounted on a Hybrid III 50th percentile neck. Four locations on the helmet shell were tested at three impact velocities for three trials, totaling 576 impact tests. Linear acceleration, rotational acceleration, and a concussion correlate were recorded for each test and a comparison between the youth and varsity helmets was made. Results showed that the age group the helmet is intended for did not have a significant effect on the impact performance of the helmet in linear acceleration, rotational acceleration, or concussion correlate. These results are likely due to the similarities in helmet design resulting from being tested to the same standard. Although it is unknown how a youth helmet should differ from a varsity helmet, differences in impact exposure, anthropometry, physiology, and injury tolerance are factors to consider. These data serve as a reference point for future youth-specific helmet design and helmet standards.